Immobilization of a keratinolytic protease from Purpureocillium lilacinum on genipin activated-chitosan beads - Cavello, Ivana Alejandra (2014)
Keratinase from Purpureocillium lilacinum LPSC # 876 was immobilized on chitosan beads using two different cross-linking agents: glutaraldehyde and genipin. For its immobilization certain parameters were optimized such as cross-linker concentration, activation time and activation temperature. Under optimum conditions, enzyme immobilization resulted to be 96 and 92.8% for glutaraldehyde and genipin, respectively, with an activity recovery reaching up to 81% when genipin was used. The immobilized keratinase showed better thermal and pH stabilities compared to the soluble form, retaining more than 85% of its activity at pH 11 and 74% at 50 °C after 1 h of incubation. The residual activity of immobilized keratinase remained more than 60% of its initial value after five hydrolytic cycles. The results in this study support that glutaraldehyde could be replaced by genipin as an alternative cross-linking eco-friendly agent for enzyme immobilization.